2021
DOI: 10.3389/fpubh.2021.753950
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technology, Knowledge Level, and Food Safety Governance: Implications for National Healthcare System

Abstract: Exploring the intrinsic relationship between digital technology and the efficiency of food safety supervision contributes to a better understanding of the role of digital technology in food safety supervision and how to maximize its influence. This study employed sample data from 31 regions in China between 2015 and 2017 for an empirical analysis of the correlation between the two and to examine the moderating effects of the knowledge levels of food producers and consumers. The results show that the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Health is a human resource, and early warning and emergency mechanisms need to be verified. Therefore, we call for establishing a national-level health strategy and social care system, flexibly implementing social distancing and epidemic investigations, giving full play to the role of the government as an information intermediary (42,43), and providing sufficient resources to support economic recovery. These open health and medical data make the data collection and analysis of health economics possible.…”
Section: Implications For Health Economicsmentioning
confidence: 99%
“…Health is a human resource, and early warning and emergency mechanisms need to be verified. Therefore, we call for establishing a national-level health strategy and social care system, flexibly implementing social distancing and epidemic investigations, giving full play to the role of the government as an information intermediary (42,43), and providing sufficient resources to support economic recovery. These open health and medical data make the data collection and analysis of health economics possible.…”
Section: Implications For Health Economicsmentioning
confidence: 99%
“…In the context of new product development and innovation, teams working in a dynamic environment encounter a rapid depreciation of technological and market knowledge due to changing customer needs, expectations, and technological proficiency. It is imperative to recognize this fact because team members’ knowledge will also become outdated and misleading, considering the rapid development of market and technological knowledge ( Moorman and Miner, 1998 ; Xi et al, 2021a ). In addition, researchers have found that, due to environmental changes, project plans, conventions, and procedures will become unproductive ( Dickson, 1992 ) and may require organizations to evaluate and change their beliefs and methods to effectively address this new and conflicting information ( Starbuck, 1996 ).…”
Section: Theoretical Analysis and Hypothesesmentioning
confidence: 99%
“…Based on existing research (21,22), this study analyzes the global trade of medical devices in detail through empirical study of…”
Section: Datamentioning
confidence: 99%